In Vivo Investigation of the Ameliorating Effect of Tempol against MIA-Induced Knee Osteoarthritis in Rats: Involvement of TGF-β1/SMAD3/NOX4 Cue - Hagar B. Abo-zalam (MDPI AG, 2021)
Osteoarthritis (OA) is a complex disease characterized by structural, functional, and metabolic deteriorations of the whole joint and periarticular tissues. In the current study, we aimed to investigate the possible effects of tempol on knee OA induced by the chemical chondrotoxic monosodium iodoacetate (MIA) which closely mimics both the pain and structural changes associated with human OA. Rats were administrated oral tempol (100 mg/kg) one week post-MIA injection (3 mg/50 μL saline) at the right knee joints for 21 consecutive days. Tempol improved motor performance and debilitated the MIA-related radiological and histological alterations. Moreover, it subsided the knee joint swelling. Tempol decreased the cartilage degradation-related biomarkers as matrix metalloproteinase-13, bone alkaline phosphatase (bone ALP), and fibulin-3. The superoxide dismutase mimetic effect of tempol was accompanied by decreased NADPH oxidase 4 (NOX4), inflammatory mediators, nuclear factor-kappa B (NF-κB), over-released transforming growth factor-β1 (TGF-β1). Tempol decreased the expression of chemokine (C-C motif) ligand 2 (CCL2). On the molecular level, tempol reduced the phosphorylated protein levels of p38 mitogen-activated protein kinase (MAPK), and small mother against decapentaplegic 3 homologs (SMAD3). These findings suggest the promising role of tempol in ameliorating MIA-induced knee OA in rats via collateral suppression of the catabolic signaling cascades including TGF-β1/SMAD3/NOX4, and NOX4/p38MAPK/NF-κB and therefore modulation of oxidative stress, catabolic inflammatory cascades, chondrocyte metabolic homeostasis.